Basic First Aid Education in Handling Emergency Cases (JURNAL PENGMAS KESTRA (JPK), 2025)
victims receive further medical treatment. However, limited first aid knowledge and skills are still common in the community and have the potential to worsen the victim's condition. Therefore, this community service activity aims to improve first aid knowledge and skills through structured and applicable education for participants at the Bethesda Saribudolok Clinic. The implementation method uses a participatory educational approach that includes interactive lectures, demonstrations, simulations, and independent practice. This activity was attended by 20 participants who also served as respondents. Evaluation was carried out through pre- and post-tests to measure knowledge gains, as well as direct observation to assess practical skills. Aspects assessed included basic first aid knowledge, initial victim examination, bleeding management, simple splinting, and recovery positions. The results of the activity showed an increase in knowledge in all aspects assessed. The average score for basic first aid knowledge increased from 55% to 88%, initial victim examination from 50% to 85%, bleeding management from 48% to 90%, simple splinting from 45% to 87%, and recovery positioning from 52% to 92%. Furthermore, observations showed an increase in practical skills, with participants being able to systematically perform initial examinations, correctly apply bandaging and splinting techniques, and position victims in the recovery position as indicated. Overall, this activity effectively increased participants' readiness as first responders and has the potential to be replicated in the wider community.